Shear Bond Strength of Colored and Sandblasted Zirconia to Ceramic Veneers Fabricated by the Pressing and Layering Techniques: An In Vitro Study - Mahsa Abbasi; Behnaz Ebadian; Negin Aminianpour (International Journal of Dentistry)
Introduction. Porcelain-veneered zirconia (PVZ) restorations are increasingly used due to their optimal esthetics and high strength. However, chipping of porcelain limits the application of PVZ restorations. The aim of this study was to assess the shear bond strength (SBS) of colored and sandblasted zirconia to ceramic veneers fabricated by the pressing and layering techniques. Materials and Methods. Sixty cubic zirconia specimens (10 × 10 × 2 mm) were assigned to three groups according to their surface treatment: (I) control, (II) sandblasting with 50 μm alumina particles (S), and (III) coloring (C). Each group was subsequently divided into two subgroups according to the porcelain-veneering technique: (I) layering (L) and (II) pressing (P). The specimens underwent 10,000 thermal cycles between 5 and 55°C, and their biaxial SBS was measured in an electromechanical universal test machine (0.5 mm/min with 2.5 kN load cell). The failure mode was also assessed under a stereomicroscope. Three samples were randomly selected from each subgroup (n = 18) for examination of zirconia-phase transformation by X-ray diffraction (XRD). Two-way and one-way ANOVA followed by the post hoc Tukey test were used to analyze statistical differences among the groups and subgroups (α = 0.05). Results. The sandblasted zirconia with press porcelain (SP) subgroup showed the highest (24.40 ± 8.16 MPa) and the colored zirconia with press porcelain (CP) subgroup showed the lowest (13.76 ±3.62 MPa) SBS. All failures were cohesive. Rate of phase transformation in layered porcelain was significantly lower than that in pressed porcelain (P<0.01). Conclusion. The sandblasted group showed the highest and the colored group showed the lowest SBS; the layered group showed higher SBS than the pressed group.